Personalized Treatment of Alcohol Dependence - Kranzler, Henry R. (Curr Psychiatry Rep, 2012)
Pharmacogenetic and adaptive treatment approaches can be used to personalize care for alcohol-dependent patients. Preliminary evidence shows that variation in the gene encoding the μ-opioid receptor moderates the response to naltrexone when used to treat alcohol dependence. Studies have also shown moderating effects of variation in the gene encoding the serotonin transporter on response to serotonergic treatment of alcohol dependence. Adaptive algorithms that modify alcohol treatment based on patients’ progress have also shown promise. Initial response to outpatient treatment appears to be a particularly important in the selection of optimal continuing care interventions. In addition, stepped-care algorithms can reduce the cost and burden of treatment while maintaining good outcomes. Finally, matching treatment to specific problems present at intake or that emerge during treatment can also improve outcomes. Although all of these effects require replication and further refinement, the future of personalized care for alcohol dependence appears bright.